Identity Politics in the Construction of Electoral Laws: A Qualitative Analysis - Jukari, Ahmad; Karimullah, Suud Sarim; Muhajir, Muhajir (Walisongo Law Review (Walrev), 2023)
This article aims to deepen the construction of general election regulations related to representation and identity politics. This research is non-doctrinal with a normative approach, using documentation studies and libraries as data sources. Research findings suggest that the electoral arrangement designs the holding of elections as a tool for preserving national identity and national interests. Although the Electoral Act does not accommodate political representation of a distinctly religious nature, its implementation involves special regulations, such as Special Autonomy for Papua Province, the Government of Aceh, and the Yogyakarta Special Territory Privileges. This regulation gives room for politics of representation based on patriotism, culture, and religion. Furthermore, the Election Act prohibits some campaign actions that could create political nuances of identity. This article is expected to contribute to a further understanding the political dynamics of representation and identity in the context of the Electoral Law in Indonesia.Artikel ini bertujuan untuk mendalami konstruksi pengaturan mengenai pemilihan umum terkait politik representasi dan politik identitas. Penelitian ini bersifat non-doktrinal dengan pendekatan normatif, menggunakan studi dokumentasi dan kepustakaan sebagai sumber data. Temuan penelitian menunjukkan bahwa pengaturan tentang Pemilu merancang penyelenggaraan pemilu sebagai alat untuk menjaga identitas nasional dan kepentingan nasional. Meskipun Undang-Undang Pemilu tidak mengakomodasi politik representasi yang bersifat kedaerahan, kesukuan, dan agama, implementasinya melibatkan regulasi khusus, seperti Otonomi Khusus Bagi Provinsi Papua, Pemerintahan Aceh, dan Keistimewaan Daerah Istimewa Yogyakarta. Regulasi khusus ini memberikan ruang untuk politik representasi berdasarkan kedaerahan, budaya, dan agama. Lebih lanjut, Undang-Undang Pemilu juga melarang sejumlah tindakan kampanye yang berpotensi menciptakan nuansa politik identitas. Artikel ini diharapkan dapat memberikan kontribusi pada pemahaman lebih lanjut tentang dinamika politik representasi dan identitas dalam konteks Undang-Undang Pemilu di Indonesia.